The Effect of Contextual Interference on Acquisition, Retention and Transfer of Volleyball Serves - Rasoul Hemayat talab; Ali Moradi; Mohammad Reza Boroumand; Ruqiya Fakhrpour (University of Tehran, 2009)
The purpose of this research was to compare block, random and randomized block training on the acquisition, retention and transfer of volleyball serves. For this purpose, 34 students of Shomal university were selected randomly and after primary rules of volleyball were explained and instructed and pretest was performed, they were divided into 3 groups (block, random and randomized block training). The subjects participated in 15 practice sessions (5 weeks, 3 sessions each week). After the training sessions, posttests including acquisition test (exactly at the end of the last session), retention and transfer tests (after one week) were performed. Kolmogorov - Smirnov (K-S) test, one-way ANOVA, and post hoc Tukey test were used to analyze the data. The results showed that in the acquisition stage, the block group significantly had better performance than the others. But in the retention test, there was no significant difference among groups. Meanwhile, the randomized-block group had significantly better performance in the transfer test.